Optimizing participatory communication in integrated village development - Yanti, Fitri; Prastiwi, Herliana (Universitas Bunda Mulia, 2024)
This research explores the role of communication in the Golden Village Movement in Lampung Province, focusing on Pasuruan Village, South Lampung. Using a qualitative and case study approach, this research analyzes the implementation of communication in the Golden Village Movement and the factors that influence its success. Through interviews, observations, and document analysis, this research reveals the importance of participatory communication in village development, as well as its impact on community participation. The results show that effective communication enables active community participation in the planning, implementation, and evaluation of development programs, such as Smart Village. Participatory communication is proven to increase the sense of belonging in the community and strengthen the relationship between the government and the community. The implications of these findings emphasize that in the absenceof inclusive and open communication, development programs are likely to experience obstacles in their implementation. Therefore, participatory communication is key to the success of the Golden Village Movement, creating harmonious relationships between government and communities and promoting inclusive, sustainable development that effectively responds to local needs.